Development and Validation of a Liquid Chromatography-Mass Spectrometry Assay for Determination of Cromolyn Sodium in Skin Permeation Studies - Miranda Kay Holman; Stacy D Brown; Dorcas Frempong; Ashana Puri; Steven Dinh (Journal of Analytical Methods in Chemistry)
Cromolyn sodium (CS) is a mast cell stabilizer administered to treat allergic diseases. A topical system would sustain its delivery and may be designed for treatment of atopic dermatitis. Established HPLC protocols for detection of CS are time consuming and intensive, indicating the need for a more streamlined method. This study aimed at developing and validating a sensitive and selective LC-MS method for quantifying CS in skin permeation studies that was less time and resource demanding. The optimized method involved an isocratic mobile phase (10 mM NH4HCO3, pH 8.0, 90% and ACN, 10%) at a flow rate of 0.25 mL/min. Detection involved direct MS/MS channels with m/z 467.0255 (precursor) and m/z 379.0517 (fragment) using argon as the collision gas. CS calibrants were prepared in PBS, pH 7.4, and methanol for validation (0.1–2.5 μg/mL). To ensure no skin interference, dermatomed porcine skin was mounted on Franz diffusion cells that were analyzed after 24 h. The skin layers were also separated, extracted in methanol, and analyzed using the developed method. Retention time was 1.9 min and 4.1 min in methanol and buffer, respectively. No interfering peaks were observed from the receptor and skin extracts, and linearity was established between 0.1 and 2.5 μg/mL. Interday and intraday accuracy and precision were within the acceptable limit of ±20% at the LLOQ and ±15% at other concentrations. Overall, the simplified, validated method showed sensitivity in detecting CS in skin without interference and was applied to demonstrate quantification of drug in skin following 4% cromolyn sodium gel exposure.